BENTUK TINDAK TUTUR BAHASA BALI PADA CERPEN “PAN ANGKLUNG GADANG DADI PAREKAN” DAN ”PAN ANGKLUNG GADANG NGELAH TUNGKED SAKTI” KARYA I. N. K. SUPATRA: KAJIAN PRAGMATIK - Ida Ayu Iran Adhiti; Gede Sidi Artajaya; Ida Ayu Pristina Pidada (Widyadari : Jurnal Pendidikan, 2022)
The short story research "Pan Angklung Gadang Dadi Parekan" and "Pan Angklung Gadang Ngelah Tungked Sakti" by I. N. K. Supatra aims to explore the speech acts contained in the two short stories. This research study uses pragmatic theory. Data were collected by using the listening method with reading and sorting techniques, namely reading the dialogues contained in the text and sorting or grouping the dialogues belonging to the locutionary, illocutionary, and perlocutionary speech acts. The results showed that the short story "Pan Angklung Gadang Dadi Parekan" found locutionary speech acts as much as one utterance, namely the utterance of Pan Angklung Gadang telling Ratu Dewa Agung saying he would carry out all the orders of Ratu Dewa Agung. There are two illocutionary tales, namely Ratu Dewa Agung telling Pan Angklung Gadang that Ratu Dewa Agung's horse rope is made of silver. Furthermore, the perlocutionary speech act found one utterance, namely the speech from Pan Angklung Gadang to Ratu Dewa Agung who said he had carried out the order well. The short story "Pan Angklung Ngelah Tungked Sakti" shows that locutionary, illocutionary, and perlocutionary speech acts are found in two utterances each. Locutionary speech acts are found in the speech of Pan Angklung Gadang which says that he has debts in the banjar. The illocutionary speech was found when the Head of the Ward warned Pan Angklung Gadang to immediately pay all his debts. Furthermore, the illocutionary speech was found when Pan Angklung Gadang showed his magic tungked at a meal with residents at his house.